2021
DOI: 10.1073/pnas.2014610118
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated expansion of pathogenic mitochondrial DNA heteroplasmies in Huntington’s disease

Abstract: Mitochondrial dysfunction is found in the brain and peripheral tissues of patients diagnosed with Huntington’s disease (HD), an irreversible neurodegenerative disease of which aging is a major risk factor. Mitochondrial function is encoded by not only nuclear DNA but also DNA within mitochondria (mtDNA). Expansion of mtDNA heteroplasmies (coexistence of mutated and wild-type mtDNA) can contribute to age-related decline of mitochondrial function but has not been systematically investigated in HD. Here, by using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 87 publications
0
28
0
Order By: Relevance
“…For example, colonic epithelium has shown that normal aging in associated with an increase in clonal fields lacking OXPHOS activity that are the result of mtDNA mutations (Taylor et al, 2003;Greaves et al, 2014). Similar findings have been observed in stomach, prostate, and small intestines of normally aged individuals, as well as blood of Huntington's disease patients (Fellous et al, 2009;Greaves et al, 2010;Wang et al, 2021).…”
Section: Clonal Expansions In Agingmentioning
confidence: 53%
“…For example, colonic epithelium has shown that normal aging in associated with an increase in clonal fields lacking OXPHOS activity that are the result of mtDNA mutations (Taylor et al, 2003;Greaves et al, 2014). Similar findings have been observed in stomach, prostate, and small intestines of normally aged individuals, as well as blood of Huntington's disease patients (Fellous et al, 2009;Greaves et al, 2010;Wang et al, 2021).…”
Section: Clonal Expansions In Agingmentioning
confidence: 53%
“…We now turn our attention to potential maladaptive consequences of sustained allostatic load, namely evidence of mitochondrial and cellular allostatic overload. In vitro and in vivo studies have shown that one of the consequences of chronic metabolic stressors, OxPhos defects, and aging is mtDNA instability, manifested as the accumulation of mtDNA defects [50][51][52][53][54] . We also recently demonstrated that mtDNA instability can be induced by OxPhos defects in this cellular lifespan system 27 .…”
Section: Chronic Gc Stress Causes Mtdna Instabilitymentioning
confidence: 99%
“…We next turned our attention to potential maladaptive consequences of sustained allostatic load, namely evidence of allostatic overload. In vitro and in vivo studies have shown that chronic metabolic stressors, primary energetic defects, and aging result in mtDNA instability, which manifest as the accumulation of mtDNA defects (53)(54)(55)(56)(57).…”
Section: Chronic Gc Stress Causes Mtdna Instabilitymentioning
confidence: 99%
“…Disruption of mitochondrial activity may be associated with PD, especially under the dysfunction of PINK1 and Parkin. PINK1 and Parkin are localized in the mitochondria ( Wang et al, 2021 ). PINK1 protects against mitochondrial dysfunction under stress by phosphorylating mitochondrial proteins.…”
Section: Human Neurological Diseases Caused By Dynamic Dysfunction Of Mitochondriamentioning
confidence: 99%
“…HTT mutants could accumulate in the body and trigger DRP1 dysfunction, leading to mitochondrial transport abnormalities and ultimately leading to neuronal apoptosis ( Song et al, 2011 ; Shirendeb et al, 2012 ). Of note, long CAG repeats in HTT could promote the age-dependent expansion of pathogenic mtDNA heteroplasmy in HD lymphoblasts ( Wang et al, 2021 ). Thus, they concluded that mtDNA quality is declining along with the HD’s process, indicating a role of HTT in mtDNA quality control.…”
Section: Human Neurological Diseases Caused By Dynamic Dysfunction Of Mitochondriamentioning
confidence: 99%